Pengaruh Rebusan Air Daun Sirsak (Annonamuricata) terhadap Penurunan Tekanan Darah pada Lansia Penderita Hipertensi di Wilayah Desa Sukawangi Kecamatan Warungkondang Kabupaten Cianjur Tahun 2023 - Ismi Rahmawati; Sancka Stella G.S; Siti Kamillah (Jurnal Ventilator, 2024)
Soursop is a traditional medicinal plant used as a therapy for hypertension. One of them is Flavonoids which work as ACE inhibitors which will inhibit the change of AIR into AIR thereby reducing the secretion of antidiuretic hormone (ADH ) thus causing a drop in blood pressure.This study aims to determine the effect of boiled soursop leaves on reducing blood pressure in elderly people with hypertension in the Sukawangi Village area, Warungkondang District, Cianjur Regency in 2023. This research uses a quantitative experimental research method using a quasi-experimental design with pre and post using a one group pre test and post test design. The population in this study was elderly people suffering from hypertension in the Sukawangi Village area, Warungkondang District, Cianjur Regency with a sample of 17 people. The analysis used is Univariate and Bivariate using the Paired Sample T test. The blood pressure of hypertensive patients before being given soursop leaf decoction treatment to obtain information on the Mean Arterial Preasure value) before being given the intervention, the mean MAP value was 124.09 mmHg from 17 respondents. After being given the intervention, the results obtained were an average MAP value of 95.24 mmHg.That there is an effect of boiled soursop leaves on reducing blood pressure in elderly people with hypertension in the Sukawangi Village area, Warungkondang District, Cianjur Regency in 2023. Should be more overcoming the problems of the Indonesian people due to the increase in patients with hypertension.